(untitled) - Moen, Ronald D. (Boston, MA., 1991)
This book presents the theories and ideas of Deming and Taguchi and shows applications of their methods to the manufacturing process. The book integrates the statistical design of experiments with statistical process control, with an emphasis on the sequential use of experiments and guidance on building the sequence.
Keywords: Quality control,Process control,Experimental design; Statistical methods,Statistical methods